Characterization of small reservoirs in Burkina Faso - Gerald, Forkuor; Cofie, Olufunke O.; Cecchi, Philippe; Barron, Jennie (CGIAR Research Program on Water, Land and Ecosystems, 2019)
Small reservoirs (SRs) are used for multiple purposes in Burkina Faso and West African agroecological landscapes (Venot et al. 2012). These SRs are used for domestic (drinking, bathing and washing) and agricultural (crop, livestock and fishery) purposes, among others (McCartney et al. 2012). However, natural processes and human-induced activities in the surrounding landscapes can be a threat to the water quality and sustainable use of SRs. In order to reduce negative effects, several projects have been designed to study different aspects of how SRs are used and impacted by natural and human-induced activities. But the number of SRs in Burkina Faso (about 1,450) (Cecchi et al. 2009) makes it practically impossible to study every single one of them. A possible solution to this is to categorize the SRs into groups in terms of their responses to the aforementioned natural and anthropogenic influences. Such categorization can provide the basis for site selection in subsequent research programs and further permit generalization (upscaling) of results obtained for selected SRs (at local scale) to many other SRs (at national scale).